ANALYSIS OF FACTORS THAT INFLUENCE CONSUMER DECISIONS IN PURCHASING PRODUCTS ONLINE AT SHOPEE (CASE STUDY OF FEB STUDENTS OF BANDAR LAMPUNG UNIVERSITY) - Chelsea Natalia Pohan; Herry Goenawan Soedarsa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The e-commerce industry is now growing rapidly in Indonesia. This is reinforced by the number of e-commerce that now dominates the Indonesian market. The large number of e-commerce in Indonesia means that consumer shopping habits have changed in this digital era and globalization. The purpose of this study is to determine the influence of cultural factors and social factors on consumer decisions in purchasing products online at Shopee. The research method used is quantitative research that uses quantitative and statistical data analysis techniques, with the main aim of testing hypotheses that have been determined by using multiple Linear Regression Test, Determination Coefficient Test, T Test, and F Test. The population and sample are students of the Faculty of Economics and Business, Bandar Lampung University, totaling 100 people. Based on the results of the study, it shows that cultural factors and social factors have a positive and significant influence on product purchase decisions online at Shopee. This shows that cultural factors and social factors simultaneously influence purchasing decisions.